(untitled) (CIPEEX, 2026)
Between January and December 2024, the Núcleo de Prática Jurídica (NPJ) at the Universidade Evangélica de Goiás (UniEVANGÉLICA), with the participation of the Law and International Relations courses, observed a continuous growth in the demand for immigration regularization services, especially from Venezuelan citizens. In response to this scenario, and with a view to overcoming barriers such as language difficulties and limited access to information, a web portal for immigrant services was designed and developed. The platform, with content in Portuguese, English, Spanish, and French, centralizes essential information and support tools, promoting social inclusion, user autonomy, and optimization of NPJ processes. This work details the design, development, and functionality of the portal, explaining how the solution was implemented to meet the identified needs.